Magnetic Resonance Imaging Characteristics Associated with Treatment Success from Basivertebral Nerve Ablation: An Aggregated Cohort Study of Multicenter Prospective Clinical Trials Data. (20th July 2022) - McCormick, Zachary L; Conger, Aaron; Smuck, Matthew; Lotz, Jeffrey C; Hirsch, Joshua A; Hickman, Colton; Harper, Katrina; Burnham, Taylor R
Abstract: Objective: Investigate associations between endplate and motion segment magnetic resonance imaging (MRI) characteristics and treatment outcomes following basivertebral nerve radiofrequency ablation (BVN RFA) in patients with clinically suspected vertebral endplate pain (VEP). Design: Aggregated cohort study of 296 participants treated with BVN RFA from three prospective clinical trials. Methods: Baseline MRI characteristics were analyzed using stepwise logistic regression to identify factors associated with treatment success. Predictive models used three definitions of treatment success: (1) ≥50% low back pain (LBP) visual analog scale (VAS), (2) ≥15-point Oswestry Disability Index (ODI), and (3) ≥50% VAS or ≥15-point ODI improvements at 3-months post-BVN RFA. Results: The presence of lumbar facet joint fluid (odds ratio [OR] 0.586) reduced the odds of BVN RFA treatment success in individuals with clinically suspected VEP. In patients with a less advanced degenerative disc disease (DDD) profile, a > 50% area of the endplate with bone marrow intensity changes (BMIC) was predictive of treatment success (OR 4.689). Both regressions areas under the curve (AUCs) were under 70%, indicating low predictive value. All other vertebral endplate, intervertebral disc, nerve roots facet joint, spinal segmental alignment, neuroforamina, lateral recesses, and central canal MRI characteristics were not associated with BVN RFA success. Conclusions: In patients with vertebrogenic low back pain with Modic changes, the presence of degenerative findings of the anterior and posterior column was not associated with a clinically important impact on BVN RFA treatment success. None of the models demonstrated strong predictive value, indicating that the use of objective imaging biomarkers (Type 1 and/or 2 Modic changes) and a correlating presentation of pain remain the most useful patient selection factors for BVN RFA.